Cognitive Interest in the Context of Information Theory of Emotions - Kulchytska, Anna (East European Journal of Psycholinguistics, 2014)
The article is devoted to the problem of cognitive interest. The theoretical aspect of the categories of interest and cognitive interest, scientific approaches to determination of these concepts are considered. Today there are two lines of interpretation of the concept of interest. One of them is based on consideration of interest as attitude. Another line is based on consideration of interest as the need transformed into behavior motive. Motivation essence of interest is traditionally considered as the basis for efficient educational and cognitive activities. Despite of great amount of researches on cognitive interest, its concept needs further investigation. This fact speaks for the article subject-matter to be topical. A variety of interpretations requires the clearing up of the concept of cognitive interest. For this purpose content-analysis and modeling methods are applied. Different scientific approaches are described to study the psychological mechanism for the development of cognitive interest. Own determinations are suggested for interest / cognitive interest. The psychological & linguistic aspect of the development of cognitive interests, their classification and importance for personality development and education process are described. The model of personality interests and the model o f cognitive interest development are presented.ReferencesKulchytska, A. V., Chertkova A. E., Myskovets E. V. (2004). Posnavatielnye interesystudientov i ih aktivaсiya [Cognitive interests of students and their activatio]. Norilsk: Norilskiyindustrialnyy institute, 24−32.Kulchytska, A. V. (2000). Aktyvizaciya piznavalnyh interesiv uchniv-vypusknykivzahalnoosvitnih shkil: dys. kandydata psiholohichnyh nauk: 19.00.07 [Activation of cognitiveinterests of comprehensive school undergraduates: Ph.D. dissertation]. Kyiv, 21−30.Kulchytska, A. V. (2011). Pisnavalnyy interes yak element osobystisnoyi aktyvnosti unavchalniy diyalnosti [Cognitive interest as an element of personality activity while education]Heneza Buttia Osobystosti. Kyiv: Informaciyno-analitychne ahenstvo, Vol. 2, 56−60.Kulchytska, A. V. (2013). Playing / Toys as the Factor for Harmonization of theDevelopment of a Child’s Outlook. Play and Playing in Early Childhood. Zagreb: Croatia, 3,137−141.Neyrobiolohiya obuchieniya i pamiati [Neurobiology of education and memory]. (1990).Simonov, Ed. Moscow: Nauka.Vygotsky, L. S. (1996). Myshlieniye i rech’: psiholohicheskiye issliedovaniya [Thinkingand speech: psychological investigations]. Moscow: Labirint.